Spatial pattern of Late Glacial and Holocene climatic and environmental development in Western Mongolia - A critical review and synthesis. (15th April 2019) - Klinge, Michael; Sauer, Daniela
Abstract: The effective humidity, resulting from the balance between evapotranspiration and precipitation, largely controls the environmental conditions under the highly continental, semi-humid to arid climate of Mongolia. Minor variations of temperature and precipitation have resulted in considerable environmental changes over the Holocene, affecting vegetation composition and density, soil formation, geomorphological activity, desertification processes, lake level and glacier distribution. Thus, various paleoclimatic archives have been investigated in several studies over the last decades. Here, we present an overview of the existing reconstructions of climatic changes over the Late Glacial and Holocene. The aim of this work is to obtain a spatially differentiated synthesis of the currently available paleoenvironmental information, and to point to existing contradictions and knowledge gaps. Our results suggest that during the Late Glacial, dry and cold conditions dominated, whereas the early Holocene was warm, and characterized by increasing humidity. 6000 years ago, the temperature began to decrease. Enhanced aridity occurred in the rain shadow east of the Altai and Khangai Mountains, pointing to increasing influence of the westerlies. In the Valley of Great Lakes, east of the Altai Mountains, the Late Glacial was characterized by high lake levels that steadily decreased over the Holocene. In the Valley of Gobi Lakes, south of the Khangai Mountains, high lake levels persisted from the early Holocene until the beginning of the mid-Holocene. In contrast, the lake level of Telmen Nuur, north of the Khangai Mountains, remained low until the end of the mid-Holocene. Periods of enhanced eolian transport and deposition occurred from the Late Glacial until the early Holocene, and again during the late Holocene. In between, during the mid-Holocene, no soil erosion by eolian and fluvial processes took place over large areas. The present state of research shows that the limited number of investigated archives and the unbalanced spatial distribution of the studied sites hamper an integrative reconstruction with appropriate spatial and temporal resolution. Paleoclimate interpretations by different authors, which were derived from the same archives or from neighboring archives in the same region diverge in paleotemperature and -humidity. Thus, paleoclimate at a regional scale of up to 100 km, as well as the timing of climate changes at a temporal scale of several centuries is still ambiguous in Mongolia. Further challenges include the multiple possible causes of lake level changes and the difficulty to distinguish (i) between climatic and anthropogenic impacts on vegetation and landscape, and (ii) between local, regional and global signals in the proxy data. In addition, there are ambiguities with respect to the ages of various materials that are obtained by radiocarbon and luminescence dating. Highlights: The proxy data for paleoclimatic reconstructions in Mongolia derived from different archives is partly inconsistent. Unbalanced spatial distribution of the studied siteshampers an integrative reconstruction with appropriate resolution. There are difficulties to distinguish between climatic and anthropogenic impacts on vegetation and landscape. Local, regional and global signals superimpose in the proxy data. Multiple causes control lake level changes in Mongolia.